Operating Lithium–Sulfur Batteries in an Ultrawide Temperature Range from ‒50 °C to 70 °C - Zhang, Hui; Chen, Jiawei; Li, Zhi; Peng, Yu; Xu, Jie; Wang, Yonggang (Advanced functional materials, 2023)
Lithium–sulfur (Li–S) batteries, boasting a high theoretical energy density, have garnered significant attention. However, their application across a wide temperature range remains hindered by the exacerbation of the polysulfide shuttle effect and sluggish reaction kinetics. Herein, this work designs a nanocomposite electrocatalyst consisting of Ni nanoparticles anchored onto carbon nanotubes (denoted as Ni@C/CNT) by directly carbonizing a metal‐organic framework/CNT (MOF/CNT) composite. This electrocatalyst is then coated onto a commercial separator, acting as a polysulfide trapper and kinetics accelerator for Li–S batteries. In this design, the Ni@C/CNT electrocatalyst features a uniform distribution of ultrafine Ni nanoparticles, derived from an MOF precursor with ordered metal sites, which facilitates polysulfide conversion at low temperature and chemisorption of polysulfides at high temperatures. Therefore, Ni@C/CNT‐modified cells can stably cycle across a wide temperature range, from ‒50 °C to 70 °C. They also demonstrate excellent performance with high‐sulfur loading (9.0 mg cm−2) at room temperature and exhibit an ultralow self‐discharge capacity attenuation of 2.59% after a 48‐h resting period. These promising results may guide the advanced design of Li–S batteries with broad operating‐temperature capabilities. A nanocomposite electrocatalyst of Ni nanoparticles anchored on carbon nanotubes (referred to Ni@C/CNT) is designed for use in Li–S batteries with wide operating temperature ranges. Benefiting from the merits of strong chemisorption and bidirectional catalytic conversion toward polysulfides, the modified cells can stably operate over a wide temperature range from ‒50 °C to 70 °C, exhibiting all‐climate operation performance.